Epidermolysis bullosa (Dowling-Meara). Disease of cytokeratins with favorable response to cyproeptadine. - Paradisi, M.; Papi, M.; Angelo, C.; Mazzanti, C.; Morricone, A.; Crescenzi, A. (European Journal of Pediatric Dermatology, 2018)
A 10-year-old girl presented from birth bullous skin lesions with herpetiform distribution, erosions of the oral mucosa, moderate hyperkeratosis of the palms and soles and a slight nail dystrofy. Blisters rapidly regressed without leaving scarring sequelae or milia. The diagnosis of Epidermolysis Bullosa Simplex (Dowling-Meara) was based on the clinical features, electron microscopy and immunohistochemical examination. The Authors discuss the etiopathogenetic mechanism of the disease and its possible relationship with epidermolytic hyperkeratosis. Finally, they report a favorable response to a new treatment.